A chemical nickel agent for circuit board surface and preparation method thereof

By using a chemical nickel agent containing a specific additive, the problem of poor uniformity and density of nickel plating layer caused by poor stability of the chemical nickel plating agent is solved, and the high density and stability of the nickel plating layer is achieved, and the brittle cracking problem is avoided.

CN119776813AInactive Publication Date: 2025-04-08SHENZHEN HUAJING SUPERCONDUCTING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962180.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor stability of the electroless nickel plating agent leads to poor uniformity and density of the formed nickel plating layer, which is prone to brittle cracking.

Method used

A chemical nickel agent with improved density and stability of nickel plating is prepared by a pharmaceutical agent containing water-soluble nickel salt, reducing agent, composite complexing agent, water-soluble lead compound, polyethylene glycol and deionized water through a specific mixing and heating stirring process.

Benefits of technology

The density and stability of the nickel plating layer are significantly improved, the brittle cracking problem of the nickel plating layer is avoided, and the uniformity and hardness of the nickel plating layer are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217450280000141
    Figure BDA0005217450280000141
  • Figure BDA0005217450280000151
    Figure BDA0005217450280000151
Patent Text Reader

Abstract

The invention relates to the technical field of chemical nickel plating solution, and discloses a chemical nickel agent applied to the surface of a circuit board and a preparation method thereof, comprising the following raw materials by weight: 20-30 parts of a water-soluble nickel salt, 15-20 parts of a reducing agent, 20-25 parts of a composite complexing agent, 0.2-0.4 parts of a water-soluble lead compound, 0.2-0.5 parts of polyethylene glycol, and 200-400 parts of deionized water. Nano cerium oxide particles are formed on the surface of a single-layer graphene oxide, significantly improving the density of a nickel coating; pre-treated carbon fibers are wound around the surface of modified graphene oxide to avoid the modified graphene oxide being added to a chemical nickel agent as an additive, causing uneven dispersion and affecting the formation of a dense and uniform nickel coating by the chemical nickel agent; nano cerium oxide can be adsorbed on the surface of a nickel coating formed by a chemical nickel agent, so that the composite material is filled into the gap of the nickel coating formed by the chemical nickel agent, thereby improving the density of the nickel coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical nickel plating solution, in particular to a chemical nickel plating agent applied to the surface of a circuit board and a preparation method thereof. Background Art

[0002] The chemical nickel reagent is a mixture of sodium hypophosphite, nickel sulfate and stabilizer. Sodium hypophosphite serves as a reducing agent, and nickel sulfate provides nickel ions. The chemical nickel reagent can promote the reduction reaction of nickel ions on the surface of the circuit board, thereby depositing a uniform, dense, smooth, corrosion-resistant, anti-discoloration and good bonding nickel coating. The nickel coating does not contain any toxic heavy metals, but the nickel coating formed by ordinary chemical nickel plating reagents is prone to brittle cracking.

[0003] Chemical nickel plating agents can produce a reduction reaction on the surface of circuit boards to deposit a nickel coating, which can effectively isolate the circuit boards from the external environment, provide excellent corrosion resistance, and also have good hardness and wear resistance; however, chemical nickel plating agents have poor stability, resulting in poor uniformity and density of the formed nickel coating. In addition, the formed nickel coating is brittle, which causes the circuit boards to be prone to brittle cracking during use. Summary of the invention

[0004] The invention provides an agent for chemical nickel plating on the surface of a circuit board and a preparation method thereof, which solves the problem that the uniformity and density of the formed nickel plating layer are poor and brittle cracking is easy to occur due to the poor stability of the chemical nickel plating agent.

[0005] The technical solution of the present invention:

[0006] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 20-30 parts of a water-soluble nickel salt, 15-20 parts of a reducing agent, 20-25 parts of a composite complexing agent, 0.2-0.4 parts of a water-soluble lead compound, 0.2-0.5 parts of polyethylene glycol, and 200-400 parts of deionized water;

[0007] The composite complexing agent is obtained by mixing ethylenediaminetetraacetic acid, phytic acid and pentaerythritol, and then mixing with the composite material;

[0008] The composite material is prepared by mixing a single layer of graphene oxide with cerium chloride heptahydrate and reacting the mixture, and then mixing the mixture with pretreated carbon fiber.

[0009] The single-layer graphene oxide is prepared by mixing graphene oxide with deionized water and subjecting the mixture to ultrasonic treatment.

[0010] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0011] The water-soluble nickel salt, the reducing agent, the complexing agent, the water-soluble lead compound, the polyethylene glycol and the deionized water are mixed, the temperature is raised to 55-65° C., and the mixture is stirred at a speed of 500-600 r / min for 30-40 minutes to obtain a chemical nickel agent.

[0012] Furthermore, the water-soluble nickel salt is nickel sulfate.

[0013] Further, the reducing agent is sodium dihydrogen hypophosphite;

[0014] Further, the water-soluble lead compound is selected from lead acetate or lead nitrate;

[0015] Furthermore, the polyethylene glycol is selected from polyethylene glycol 200 or polyethylene glycol 400.

[0016] Further, the composite complexing agent is prepared by the following steps:

[0017] A1. Add graphene oxide to deionized water, stir evenly, place in a 45-55°C water bath, ultrasonically treat at 40-60KHz for 20-40min, filter, wash, and dry to obtain a single layer of graphene oxide;

[0018] A2. Add cerium chloride heptahydrate to deionized water, stir until the cerium chloride heptahydrate is dissolved, add a monolayer of graphene oxide and sodium hydroxide, stir at 200-300 r / min for 30-40 min, place in a reactor, stir at 110-130 ° C for 6-8 h, cool to room temperature, take out the solid, wash the solid, and dry it to obtain modified graphene oxide;

[0019] A3. Add the carbon fiber to Tris-HCl buffer, stir evenly, add dopamine, stir for 3-4h, filter, wash, and dry to obtain pretreated carbon fiber;

[0020] A4. Add the modified graphene oxide and pretreated carbon fiber to ethanol, stir at 30-50°C for 20-30min, raise the temperature to 85-90°C, continue stirring until the ethanol evaporates, take out, wash, and dry to obtain a composite material;

[0021] A5. Add ethylenediaminetetraacetic acid and phytic acid to ethanol, stir evenly, add hydrochloric acid, stir at 70-80°C for 20-30 min, add pentaerythritol, continue stirring and reacting for 20-30 min, stir evenly at 85-90°C to obtain a precipitate, and after drying the precipitate, obtain an ethylenediaminetetraacetic acid derivative;

[0022] A6. Add the ethylenediaminetetraacetic acid derivative and the composite material to ethanol, stir at 30-50°C for 20-30 minutes, heat to 85-90°C, stir evenly, take out, wash and dry to obtain a composite complexing agent.

[0023] Furthermore, in the above-mentioned reaction process A1, graphene oxide is mixed with deionized water, and after ultrasonic treatment, the graphene oxide can weaken the force between graphene oxide sheets under the action of ultrasound, so that the graphene oxide is peeled off to form a single layer of graphene oxide.

[0024] Furthermore, in the above-mentioned A2 reaction process, the oxygen-containing functional groups contained on the surface of the monolayer graphene oxide can be combined with the cerium ions in the cerium chloride heptahydrate through chemical bonds, so that the cerium ions are deposited on the surface of the monolayer graphene oxide, and the cerium ions can also be combined with the hydroxide ions in the sodium hydroxide, and the formed hydroxide is deposited on the surface of the monolayer graphene oxide. The reaction is stirred at 110-130°C, so that the hydroxide deposited on the surface of the monolayer graphene oxide is thermally decomposed to form an oxide. As the reaction proceeds, the oxide crystals grow to form nano-cerium oxide, thereby forming nano-cerium oxide particles on the surface of the monolayer graphene oxide to form modified graphene oxide.

[0025] Furthermore, during the above reaction A3, in the Tris-HCl buffer, dopamine can self-polymerize on the surface of the carbon fiber to form polydopamine, so that the carbon fiber has better adhesion, which is beneficial for the carbon fiber to adhere to the surface of the modified graphene oxide.

[0026] Furthermore, during the above-mentioned A4 reaction process, the surface of the pretreated carbon fiber contains a polydopamine layer, and the phenolic hydroxyl groups contained therein can combine with the modified graphene oxide, so that the pretreated carbon fiber acts on the surface of the modified graphene oxide to form a composite material.

[0027] Furthermore, during the above reaction A5, the carboxyl group contained in EDTA can be chemically bonded with the phosphorus hydroxyl group in phytic acid, so that EDTA is grafted onto the phytic acid molecule, and EDTA can also react with the hydroxyl group of pentaerythritol to form EDTA derivatives.

[0028] Furthermore, during the above reaction A6, the oxygen-containing functional groups contained in the ethylenediaminetetraacetic acid derivatives can be combined with the phenolic hydroxyl groups in the composite material through chemical bonds, so that the ethylenediaminetetraacetic acid derivatives are grafted on the surface of the composite material to form a composite complexing agent.

[0029] Furthermore, in step A1, the ratio of graphene oxide to deionized water is (1-2) g: (45-55) mL.

[0030] Furthermore, in step A2, the ratio of the cerium chloride heptahydrate, deionized water, monolayer graphene oxide and sodium hydroxide is (6-7) g: (75-85) mL: (5-6) g: (2-3) g.

[0031] Furthermore, in step A3, the ratio of the carbon fiber, Tris-HCl buffer and dopamine is (2-3) g: (45-55) mL: (0.3-0.7) g.

[0032] Furthermore, in step A4, the ratio of the modified graphene oxide, pretreated carbon fiber and ethanol is (2-3) g: (2-4) g: (35-45) mL.

[0033] Furthermore, in step A5, the ratio of ethylenediaminetetraacetic acid, phytic acid, ethanol, hydrochloric acid and pentaerythritol is (2-3) g: (1-1.4) g: (25-35) mL: (0.1-0.3) mL: (1-2) g.

[0034] Furthermore, in step A6, the ratio of the ethylenediaminetetraacetic acid derivative, the composite material and the ethanol is (8-9) g:(5-6) g:(35-45) mL.

[0035] Further, the reinforcing filler is prepared by the following steps:

[0036] B1. Add kaolin and glucose to ethanol, stir at 60-80°C for 25-35min, filter, wash, dry, mix with potassium hydroxide aqueous solution, stir evenly, carbonize at 750-850°C for 1-3h, cool to room temperature, take out, wash, and dry to obtain modified kaolin;

[0037] B2. Add itaconic acid and phytic acid to deionized water, stir evenly, react at 60-70°C for 25-35 minutes, add modified kaolin, stir evenly, add ammonium persulfate and polyethylene glycol, react at 90-100°C for 30-40 minutes, cool to room temperature, filter, wash and dry to obtain a reinforced filler.

[0038] Furthermore, during the above-mentioned B1 reaction process, the hydroxyl groups contained on the surface of kaolin can be chemically bonded with the oxygen-containing functional groups in glucose, so that the glucose is coated on the surface of kaolin. After high-temperature carbonization, the glucose is thermally decomposed to form a dense carbon layer. The potassium hydroxide aqueous solution is used as an activator to form pores on the surface of the dense carbon layer, thereby realizing the synthesis of porous carbon on the surface of kaolin. The synthesized porous carbon has high adsorption properties and can adsorb and fix impurities in kaolin.

[0039] Furthermore, in the above-mentioned B2 reaction process, itaconic acid and phytic acid are combined through chemical bonds, and ammonium persulfate is used as a catalyst to polymerize the double bonds carried by itaconic acid to form a polymer. The carboxyl and hydroxyl groups carried by the formed polymer can be combined with the oxygen-containing functional groups on the surface of the modified kaolin through chemical bonds to form a cross-linked network structure, i.e., a reinforcing filler.

[0040] Furthermore, in step B1, the ratio of kaolin, glucose, ethanol and potassium hydroxide aqueous solution is (5-6) g: (6-7) g: (50-70) mL: (8-12) mL.

[0041] Furthermore, in step B2, the usage ratio of itaconic acid, phytic acid, deionized water, modified kaolin, ammonium persulfate and polyethylene glycol is (1-2) g: (1-3) g: (45-55) mL: (5-6) g: (0.1-0.3) g: (1-2) g.

[0042] The present invention has the following beneficial effects:

[0043] (1) In the technical scheme of the present invention, nano-cerium oxide particles are formed on the surface of a monolayer graphene oxide to form a modified graphene oxide. The monolayer graphene oxide serves as a carrier of the nano-cerium oxide particles and can load a large amount of nano-cerium oxide, thereby avoiding the agglomeration of the nano-cerium oxide and affecting the formation of a dense and uniform nickel coating by the chemical nickel agent. The formed nano-cerium oxide can be adsorbed on the grain boundary trapping area of ​​the nickel coating, thereby increasing the surface energy of the nickel crystal growth, playing a role in refining the nickel crystals, and significantly increasing the density of the nickel coating. Dopamine can self-polymerize on the surface of the carbon fiber to form polydopamine, so that the carbon fiber has better adhesion, which is beneficial for the adhesion of the carbon fiber to the surface of the modified graphene oxide.

[0044] (2) In the technical solution of the present invention, the pretreated carbon fiber acts on the surface of the modified graphene oxide to form a composite material. The pretreated carbon fiber has an excellent aspect ratio and is wound on the surface of the modified graphene oxide, giving the modified graphene oxide excellent dispersibility, thereby avoiding the modified graphene oxide being added as an additive to the chemical nickel agent and being unevenly dispersed, thereby affecting the chemical nickel agent from forming a dense and uniform nickel coating. The composite material contains carbon fiber and graphene oxide, which can absorb stress and avoid the formed nickel coating being brittle, thereby causing the circuit board to be prone to brittle cracking during use. In addition, the composite material contains nano-cerium oxide particles. Under the action of nano-cerium oxide, the nano-cerium oxide can be adsorbed onto the surface of the nickel coating formed by the chemical nickel agent, thereby filling the composite material into the gaps in the nickel coating formed by the chemical nickel agent, thereby improving the density of the nickel coating.

[0045] (3) In the technical solution of the present invention, ethylenediaminetetraacetic acid reacts with phytic acid and pentaerythritol to form ethylenediaminetetraacetic acid derivatives, which expand the molecular chain of ethylenediaminetetraacetic acid, improve the complexing effect of ethylenediaminetetraacetic acid on nickel ions, improve the stability of chemical nickel reagent, and facilitate the formation of a uniform and dense nickel plating layer; the ethylenediaminetetraacetic acid derivatives interact with the composite material, so that the ethylenediaminetetraacetic acid derivatives are grafted on the surface of the composite material, further improving the dispersibility of the composite material in the chemical nickel reagent. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.

[0048] The water-soluble nickel salt is nickel sulfate.

[0049] The reducing agent is sodium dihydrogen hypophosphite.

[0050] The water-soluble lead compound is lead nitrate.

[0051] The polyethylene glycol was polyethylene glycol 400.

[0052] The diameter of graphene oxide is 0.5 μm.

[0053] The diameter of the carbon fiber is 20-30nm and the length of the carbon fiber is 1-2μm.

[0054] Example 1

[0055] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 20 parts of nickel sulfate, 15 parts of sodium dihydrogen hypophosphite, 20 parts of a composite complexing agent, 0.2 parts of lead nitrate, 0.2 parts of polyethylene glycol 400, and 200 parts of deionized water;

[0056] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0057] Nickel sulfate, sodium dihydrogen hypophosphite, a complex chelating agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, the temperature is raised to 55° C., and the mixture is stirred at a speed of 500 r / min for 30 minutes to obtain a chemical nickel agent.

[0058] The composite complexing agent is prepared by the following steps:

[0059] A1. Add 1 g of graphene oxide to 45 mL of deionized water, stir evenly, place in a 45°C water bath, ultrasonically treat at 40 kHz for 20 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0060] A2. Add 6 g of cerium chloride heptahydrate to 75 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 5 g of monolayer graphene oxide and 2 g of sodium hydroxide, stir at 200 r / min for 30 min, place in a reactor, stir and react at 110 ° C for 6 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0061] A3. Add 2 g of carbon fiber to 45 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.3 g of dopamine, stir for 3 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0062] A4. 2 g of modified graphene oxide and 2 g of pretreated carbon fiber were added to 35 mL of ethanol, stirred at 30 ° C for 20 min, heated to 85 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0063] A5. 2 g of ethylenediaminetetraacetic acid and 1 g of phytic acid were added to 25 mL of ethanol, stirred evenly, 0.1 mL of 1.5 mol / L hydrochloric acid was added, stirred at 70°C for 20 min, 1 g of pentaerythritol was added, and the reaction was continued with stirring for 20 min. The ethanol was removed at 85°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0064] A6. Add 8 g of ethylenediaminetetraacetic acid derivative and 5 g of the composite material to 35 mL of ethanol, stir at 30°C for 20 min, heat to 85°C, continue stirring until the ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0065] Example 2

[0066] A chemical nickel reagent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 25 parts of nickel sulfate, 18 parts of sodium dihydrogen hypophosphite, 23 parts of a composite complexing agent, 0.3 parts of lead nitrate, 0.3 parts of polyethylene glycol 400, and 300 parts of deionized water;

[0067] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0068] Nickel sulfate, sodium dihydrogen hypophosphite, a complex chelating agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, the temperature is raised to 60° C., and the mixture is stirred at a speed of 550 r / min for 35 minutes to obtain a chemical nickel agent.

[0069] The composite complexing agent is prepared by the following steps:

[0070] A1. Add 1.5 g of graphene oxide to 50 mL of deionized water, stir evenly, place in a 50°C water bath, ultrasonically treat at 50 KHz for 30 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0071] A2. Add 6.5 g of cerium chloride heptahydrate to 80 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 5.5 g of monolayer graphene oxide and 2.5 g of sodium hydroxide, stir at 250 r / min for 35 min, place in a reactor, stir and react at 120 ° C for 7 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0072] A3. Add 2.5 g of carbon fiber to 50 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.5 g of dopamine, stir for 3.5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0073] A4. 2.5 g of modified graphene oxide and 3 g of pretreated carbon fiber were added to 40 mL of ethanol, stirred at 40 ° C for 25 min, heated to 88 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0074] A5. 2.5 g of ethylenediaminetetraacetic acid and 1.2 g of phytic acid were added to 30 mL of ethanol, stirred evenly, 0.2 mL of 1.5 mol / L hydrochloric acid was added, stirred at 75°C for 25 min, 1.5 g of pentaerythritol was added, and the reaction was continued with stirring for 25 min. The ethanol was removed at 88°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0075] A6. Add 8.5 g of ethylenediaminetetraacetic acid derivative and 5.5 g of composite material to 40 mL of ethanol, stir at 40°C for 25 min, heat to 88°C, continue stirring until ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0076] Example 3

[0077] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 30 parts of nickel sulfate, 20 parts of sodium dihydrogen hypophosphite, 25 parts of a composite complexing agent, 0.4 parts of lead nitrate, 0.5 parts of polyethylene glycol 400, and 400 parts of deionized water;

[0078] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0079] Nickel sulfate, sodium dihydrogen hypophosphite, a composite complexing agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, heated to 65° C., and stirred at a speed of 600 r / min for 40 minutes to obtain a chemical nickel agent.

[0080] The composite complexing agent is prepared by the following steps:

[0081] A1. Add 2 g of graphene oxide to 55 mL of deionized water, stir evenly, place in a 55°C water bath, ultrasonically treat at 60 kHz for 40 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0082] A2. Add 7 g of cerium chloride heptahydrate to 85 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 6 g of monolayer graphene oxide and 3 g of sodium hydroxide, stir at 300 r / min for 40 min, place in a reactor, stir and react at 130 ° C for 8 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0083] A3. Add 3 g of carbon fiber to 55 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.7 g of dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0084] A4. 3 g of modified graphene oxide and 4 g of pretreated carbon fiber were added to 45 mL of ethanol, stirred at 50 ° C for 30 min, heated to 90 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0085] A5. 3 g of ethylenediaminetetraacetic acid and 1.4 g of phytic acid were added to 35 mL of ethanol, stirred evenly, 0.3 mL of 1.5 mol / L hydrochloric acid was added, stirred at 80°C for 30 min, 2 g of pentaerythritol was added, and the reaction was continued with stirring for 30 min. The ethanol was removed at 90°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0086] A6. Add 9 g of ethylenediaminetetraacetic acid derivative and 6 g of the composite material to 45 mL of ethanol, stir at 50°C for 30 min, heat to 90°C, continue stirring until the ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0087] Comparative Example 1

[0088] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 30 parts of nickel sulfate, 20 parts of sodium dihydrogen hypophosphite, 25 parts of a composite complexing agent, 0.4 parts of lead nitrate, 0.5 parts of polyethylene glycol 400, and 400 parts of deionized water;

[0089] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0090] Nickel sulfate, sodium dihydrogen hypophosphite, a composite complexing agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, heated to 65° C., and stirred at a speed of 600 r / min for 40 minutes to obtain a chemical nickel agent.

[0091] The composite complexing agent is prepared by the following steps:

[0092] A1. Add 2 g of graphene oxide to 55 mL of deionized water, stir evenly, place in a 55°C water bath, ultrasonically treat at 60 kHz for 40 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0093] A2. Add 3 g of carbon fiber to 55 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.7 g of dopamine, stir for 4 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0094] A3. 3 g of monolayer graphene oxide and 4 g of pretreated carbon fiber were added to 45 mL of ethanol, stirred at 50 ° C for 30 min, heated to 90 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0095] A4. 3 g of ethylenediaminetetraacetic acid and 1.4 g of phytic acid were added to 35 mL of ethanol, stirred evenly, 0.3 mL of 1.5 mol / L hydrochloric acid was added, stirred at 80°C for 30 min, 2 g of pentaerythritol was added, and the reaction was continued with stirring for 30 min. The ethanol was removed at 90°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0096] A5. Add 9 g of ethylenediaminetetraacetic acid derivative and 6 g of the composite material to 45 mL of ethanol, stir at 50°C for 30 min, heat to 90°C, continue stirring until the ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0097] Comparative Example 2

[0098] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 30 parts of nickel sulfate, 20 parts of sodium dihydrogen hypophosphite, 25 parts of a composite complexing agent, 0.4 parts of lead nitrate, 0.5 parts of polyethylene glycol 400, and 400 parts of deionized water;

[0099] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0100] Nickel sulfate, sodium dihydrogen hypophosphite, a composite complexing agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, heated to 65° C., and stirred at a speed of 600 r / min for 40 minutes to obtain a chemical nickel agent.

[0101] The composite complexing agent is prepared by the following steps:

[0102] A1. Add 2 g of graphene oxide to 55 mL of deionized water, stir evenly, place in a 55°C water bath, ultrasonically treat at 60 kHz for 40 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0103] A2. Add 7 g of cerium chloride heptahydrate to 85 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 6 g of monolayer graphene oxide and 3 g of sodium hydroxide, stir at 300 r / min for 40 min, place in a reactor, stir and react at 130 ° C for 8 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0104] A3. 3 g of ethylenediaminetetraacetic acid and 1.4 g of phytic acid were added to 35 mL of ethanol, stirred evenly, 0.3 mL of 1.5 mol / L hydrochloric acid was added, stirred at 80°C for 30 min, 2 g of pentaerythritol was added, and the reaction was continued with stirring for 30 min. The ethanol was removed at 90°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0105] A4. Add 9 g of ethylenediaminetetraacetic acid derivative and 6 g of modified graphene oxide to 45 mL of ethanol, stir at 50°C for 30 min, heat to 90°C, continue stirring until ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0106] Comparative Example 3

[0107] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 30 parts of nickel sulfate, 20 parts of sodium dihydrogen hypophosphite, 25 parts of a composite complexing agent, 0.4 parts of lead nitrate, 0.5 parts of polyethylene glycol 400, and 400 parts of deionized water;

[0108] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0109] Nickel sulfate, sodium dihydrogen hypophosphite, a composite complexing agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, heated to 65° C., and stirred at a speed of 600 r / min for 40 minutes to obtain a chemical nickel agent.

[0110] The composite complexing agent is prepared by the following steps:

[0111] A1. Add 2 g of graphene oxide to 55 mL of deionized water, stir evenly, place in a 55°C water bath, ultrasonically treat at 60 kHz for 40 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0112] A2. Add 7 g of cerium chloride heptahydrate to 85 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 6 g of monolayer graphene oxide and 3 g of sodium hydroxide, stir at 300 r / min for 40 min, place in a reactor, stir and react at 130 ° C for 8 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0113] A3. Add 3 g of carbon fiber to 55 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.7 g of dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0114] A4. 3 g of modified graphene oxide and 4 g of pretreated carbon fiber were added to 45 mL of ethanol, stirred at 50 ° C for 30 min, heated to 90 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0115] A5. 3 g of ethylenediaminetetraacetic acid and 2 g of pentaerythritol were added to 35 mL of ethanol, stirred evenly, 0.3 mL of 1.5 mol / L hydrochloric acid was added, stirred at 80°C for 30 min, and the ethanol was removed at 90°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0116] A6. Add 9 g of ethylenediaminetetraacetic acid derivative and 6 g of the composite material to 45 mL of ethanol, stir at 50°C for 30 min, heat to 90°C, continue stirring until the ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0117] Comparative Example 4

[0118] A chemical nickel agent for use on the surface of a circuit board, comprising the following raw materials in parts by weight: 30 parts of nickel sulfate, 20 parts of sodium dihydrogen hypophosphite, 25 parts of a composite complexing agent, 0.4 parts of lead nitrate, 0.5 parts of polyethylene glycol 400, and 400 parts of deionized water;

[0119] A method for preparing an agent for chemical nickel on the surface of a circuit board comprises the following steps:

[0120] Nickel sulfate, sodium dihydrogen hypophosphite, a composite complexing agent, lead nitrate, polyethylene glycol 400 and deionized water are mixed, heated to 65° C., and stirred at a speed of 600 r / min for 40 minutes to obtain a chemical nickel agent.

[0121] The composite complexing agent is prepared by the following steps:

[0122] A1. Add 2 g of graphene oxide to 55 mL of deionized water, stir evenly, place in a 55°C water bath, ultrasonically treat at 60 kHz for 40 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a single layer of graphene oxide;

[0123] A2. Add 7 g of cerium chloride heptahydrate to 85 mL of deionized water, stir until the cerium chloride heptahydrate is dissolved, add 6 g of monolayer graphene oxide and 3 g of sodium hydroxide, stir at 300 r / min for 40 min, place in a reactor, stir and react at 130 ° C for 8 h, cool to room temperature, take out the solid, wash the solid with deionized water until the pH of the washing liquid is neutral, and dry in an oven at 90 ° C for 30 min to obtain modified graphene oxide;

[0124] A3. Add 3 g of carbon fiber to 55 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.7 g of dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated carbon fiber;

[0125] A4. 3 g of modified graphene oxide and 4 g of pretreated carbon fiber were added to 45 mL of ethanol, stirred at 50 ° C for 30 min, heated to 90 ° C, and continued to stir until the ethanol evaporated, taken out, washed with deionized water three times, and dried in an oven at 60 ° C for 15 min to obtain a composite material;

[0126] A5. 3 g of ethylenediaminetetraacetic acid and 1.4 g of phytic acid were added to 35 mL of ethanol, stirred evenly, 0.3 mL of 1.5 mol / L hydrochloric acid was added, stirred at 80°C for 30 min, and the ethanol was removed at 90°C using a rotary evaporator to obtain a precipitate, which was dried in an oven at 60°C for 10 min to obtain an ethylenediaminetetraacetic acid derivative;

[0127] A6. Add 9 g of ethylenediaminetetraacetic acid derivative and 6 g of the composite material to 45 mL of ethanol, stir at 50°C for 30 min, heat to 90°C, continue stirring until the ethanol evaporates, take out, wash with deionized water 3 times, and dry in an oven at 80°C for 8 min to obtain a composite complexing agent.

[0128] The performance of the chemical nickel reagents prepared in Examples 1-3 and Comparative Examples 1-4 is now tested.

[0129] The circuit board was cleaned with 100 g / L sulfuric acid solution for 3 minutes, dried at 70°C for 10 minutes, immersed in the chemical nickel agent prepared above, nickel precipitated at 80°C for 25 minutes, taken out, washed with water, and dried to obtain a nickel plating layer.

[0130] Use an electron microscope to observe the surface of the nickel plating to detect the uniformity and density of the nickel plating surface; bind the nickel plating to the copper wire or aluminum wire, and after standing for 48 hours, remove the copper wire and aluminum wire to observe whether the plating of the circuit board has brittle cracking problems;

[0131] Hardness test: Use a microhardness tester to test the hardness of the nickel coating.

[0132] The test results are shown in Table 1 below.

[0133] Table 1 Performance test of chemical nickel prepared in Examples 1-3 and Comparative Examples 1-4

[0134]

[0135]

[0136] It can be seen from the data in Table 1 that the chemical nickel reagents prepared in Examples 1-3 have good stability, and the nickel coating formed by the reagents is uniform, dense, and not prone to brittle cracking.

[0137] In Comparative Example 1, the modified graphene oxide is replaced by a composite complexing agent prepared by a single-layer graphene oxide, and added to the chemical nickel agent. The uniformity and hardness of the nickel plating layer produced by the agent decrease, and it is easy to crack. This proves that nano-cerium oxide particles are formed on the surface of the single-layer graphene oxide, which significantly improves the density of the nickel plating. In addition, nano-cerium oxide can be adsorbed to the surface of the nickel plating formed by the chemical nickel agent, and then filled into the gaps in the nickel plating formed by the chemical nickel agent, thereby improving the density of the nickel plating.

[0138] In Comparative Example 2, the composite complexing agent prepared without adding carbon fiber was added to the chemical nickel agent. The uniformity and hardness of the nickel plating layer produced by the agent decreased, and it was easy to crack. This proves that the pretreated carbon fiber is wrapped around the surface of the modified graphene oxide, giving the modified graphene oxide excellent dispersibility, and the carbon fiber and graphene oxide can absorb stress, avoiding the problem that the formed nickel plating is brittle and easy to crack.

[0139] Comparative Examples 3 and 4 are composite complexing agents prepared without adding phytic acid and pentaerythritol. When added to the chemical nickel agent, the uniformity of the nickel plating layer produced by the agent decreases, indicating that ethylenediaminetetraacetic acid reacts with phytic acid and pentaerythritol to expand the molecular chain of ethylenediaminetetraacetic acid, improve the complexing effect of ethylenediaminetetraacetic acid on nickel ions, improve the stability of the chemical nickel agent, and is conducive to forming a uniform and dense nickel plating layer.

[0140] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0141] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A chemical nickel agent applied to the surface of a circuit board, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of water-soluble nickel salt, 15-20 parts of reducing agent, 20-25 parts of composite complexing agent, 0.2-0.4 parts of water-soluble lead compound, 0.2-0.5 parts of polyethylene glycol, and 200-400 parts of deionized water; The composite complexing agent is obtained by mixing ethylenediaminetetraacetic acid, phytic acid and pentaerythritol, and then mixing with the composite material; The composite material is prepared by mixing a single layer of graphene oxide with cerium chloride heptahydrate and reacting the mixture, and then mixing the mixture with pretreated carbon fiber. The single-layer graphene oxide is prepared by mixing graphene oxide with deionized water and subjecting the mixture to ultrasonic treatment.

2. The chemical nickel agent for use on the surface of a circuit board according to claim 1, characterized in that: The composite complexing agent is prepared by the following steps: A1. Add graphene oxide to deionized water, stir evenly, place in a 45-55°C water bath, ultrasonically treat at 40-60KHz for 20-40min, filter, wash, and dry to obtain a single layer of graphene oxide; A2. Add cerium chloride heptahydrate to deionized water, stir until the cerium chloride heptahydrate is dissolved, add a monolayer of graphene oxide and sodium hydroxide, stir at 200-300 r / min for 30-40 min, place in a reactor, stir at 110-130 ° C for 6-8 h, cool to room temperature, take out the solid, wash the solid, and dry it to obtain modified graphene oxide; A3. Add the carbon fiber to Tris-HCl buffer, stir evenly, add dopamine, stir for 3-4h, filter, wash, and dry to obtain pretreated carbon fiber; A4. Add the modified graphene oxide and pretreated carbon fiber to ethanol, stir at 30-50°C for 20-30min, raise the temperature to 85-90°C, continue stirring until the ethanol evaporates, take out, wash, and dry to obtain a composite material; A5. Add ethylenediaminetetraacetic acid and phytic acid to ethanol, stir evenly, add hydrochloric acid, stir at 70-80°C for 20-30 min, add pentaerythritol, continue stirring and reacting for 20-30 min, stir evenly at 85-90°C to obtain a precipitate, and after drying the precipitate, obtain an ethylenediaminetetraacetic acid derivative; A6. Add the ethylenediaminetetraacetic acid derivative and the composite material to ethanol, stir at 30-50°C for 20-30 minutes, heat to 85-90°C, stir evenly, take out, wash and dry to obtain a composite complexing agent.

3. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A1, the ratio of graphene oxide to deionized water is (1-2) g: (45-55) mL.

4. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A2, the ratio of the cerium chloride heptahydrate, deionized water, monolayer graphene oxide and sodium hydroxide is (6-7) g: (75-85) mL: (5-6) g: (2-3) g.

5. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A3, the ratio of the carbon fiber, Tris-HCl buffer and dopamine is (2-3) g: (45-55) mL: (0.3-0.7) g.

6. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A4, the ratio of the modified graphene oxide, pretreated carbon fiber and ethanol is (2-3) g: (2-4) g: (35-45) mL.

7. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A5, the ratio of ethylenediaminetetraacetic acid, phytic acid, ethanol, hydrochloric acid and pentaerythritol is (2-3) g: (1-1.4) g: (25-35) mL: (0.1-0.3) mL: (1-2) g.

8. The chemical nickel agent for use on the surface of a circuit board according to claim 2, characterized in that: In step A6, the ratio of the ethylenediaminetetraacetic acid derivative, the composite material and the ethanol is (8-9) g: (5-6) g: (35-45) mL.

9. A method for preparing an agent for chemical nickel applied to the surface of a circuit board as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: The water-soluble nickel salt, the reducing agent, the complexing agent, the water-soluble lead compound, the polyethylene glycol and the deionized water are mixed, the temperature is raised to 55-65° C., and the mixture is stirred at a speed of 500-600 r / min for 30-40 minutes to obtain a chemical nickel agent.